Differential Effects of Phosphatidylinositol 4-Kinase (PI4K) and 3-Kinase (PI3K) Inhibitors on Stomatal Responses to Environmental Signals - Takahashi, Sho; Monda, Keina; Higaki, Takumi; Hashimoto-Sugimoto, Mimi; Negi, Juntaro; Hasezawa, Seiichiro; Iba, Koh (Frontiers in Plant Science, 2017)
Specific cellular components including products of phosphatidylinositol (PI) metabolism play an important role as signaling molecules in stomatal responses to environmental signals. In this study, pharmacological inhibitors of a set of cellular components, including PI4-kinase (PI4K) and PI3K, were used to investigate stomatal closure in response to CO2, darkness, and abscisic acid (ABA). Treatment with PAO, a specific inhibitor of PI4K, specifically inhibited the stomatal response to CO2 compared with that to darkness and ABA. In contrast, treatment with LY294002, a PI3K-specific inhibitor, specifically inhibited the stomatal response to darkness compared with that to CO2 and ABA. The specific inhibitory effects of PAO and LY294002 were also observed as changes in the spatial density of dot-like structures labeled by green fluorescent protein-tagged PATROL1, a protein that controls stomatal aperture possibly via regulation of H+-ATPase amount in guard cell plasma membranes. Our results suggest an important role for PI4K and PI3K in the CO2 and darkness signal transduction pathways, respectively, that mediate PATROL1 dynamics.